Cachexia as a major public health problem: frequent, costly, and deadly. Issue 3 (29th March 2013) - Farkas, Jerneja; von Haehling, Stephan; Kalantar-Zadeh, Kamyar; Morley, John E.; Anker, Stefan D.; Lainscak, Mitja
Abstract : Perception of healthy body size and composition differs considerably across the globe, ethnic groups, cultures, and even inside medical community. Although the concept of ideal body weight has evolved over the past decades, the observation that weight loss can have more deleterious effects within a short‐term period than weight gain has remained rather consistent. Weight loss, as a prelude to cachexia, occurs frequently in a variety of disease states and meets the requirements of a global public health problem. Consequently, interventions to prevent and control chronic diseases require a comprehensive approach that targets a population as a whole and includes both prevention and treatment strategies. Around the globe, cachexia awareness campaigns and expanding the current public health priorities to highlight the cachexia magnitude and areas of interventions is necessary. Simultaneously, scientific efforts should provide us with more reliable estimates of body wasting and cachexia as well as pathophysiology of cachexia‐associated death. As certain proportion of patients will, irrespective of preventive measures, eventually develop cachexia, a quest for effective remedy remains vital.